Shigella flexneri invasion plasmid antigens B and C: epitope location and characterization with monoclonal antibodies. - Mills, J A (1988)
Invasion plasmid antigens B (IpaB) and C (IpaC) are associated with the ability of shigellae to invade cultured mammalian cells. Monoclonal antibodies against IpaB and IpaC polypeptides were produced and used in a whole-cell enzyme-linked immunosorbent assay to show that both IpaB and IpaC polypeptides were exposed on the surface of virulent shigellae. Moreover, these surface epitopes were shown to be highly conserved among different serotypes of Shigella spp. and enteroinvasive Escherichia coli. Cross-reactive epitopes were not found on noninvasive Shigella strains or on other enteric bacteria including Salmonella, Yersinia, Campylobacter, Vibrio, and Aeromonas spp. and various pathogenic strains of E. coli. The monoclonal antibodies were used in competitive binding assays to define three unique epitopes of the IpaB polypeptide and four unique epitopes of the IpaC polypeptide. Epitope locations and their corresponding DNA-encoding regions were defined by examining the IpaB and IpaC products expressed by lambda gt11 recombinants and by constructing a genetic map of the insert DNAs of these recombinants. Three IpaB epitopes (2F1, 1H4, 4C8) were found to be encoded on three contiguous DNA regions comprising a 700-base-pair (bp) segment that corresponded to the amino-terminal end of the IpaB polypeptide. Similarly, a 640-bp DNA segment that corresponded to the amino-terminal end of the IpaC polypeptide was found to encode three clustered IpaC epitopes (5H1, 9B6, 5B1). Approximately 50 bp downstream from this region a fourth IpaC epitope-encoding region (2G2) was found. The effect of the monoclonal antibodies on plaque formation by virulent Shigella flexneri on a monolayer of cultured mammalian cells (a sensitive measure of invasiveness) was determined. Only the IpaB-specific monoclonal antibody 2F1 was able to reduce the plaque-forming capacity by greater than 50%, suggesting that this epitope of the IpaB polypeptide is involved in the invasion process.